2017
DOI: 10.1200/jco.2017.35.15_suppl.3591
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of clinical outcomes in resected stage II and III colorectal cancer (CRC) through deep sequencing of circulating tumor DNA (ctDNA).

Abstract: 3591 Background: Adjuvant chemotherapy is offered to most pts with Stage III CRC, and to a subset with Stage II disease deemed at high-risk for recurrence. Nevertheless, risk stratification strategies remain suboptimal. Detection of minimal residual disease (MRD) through ctDNA analysis has been shown to identify pts at high recurrence risk in Stage II CRC, but not Stage III disease. Methods: The next-generation sequencing based AVENIO ctDNA Surveillance Kit (Research Use Only) was used to identify single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Molecular Residual Disease (MRD). ctDNA has been shown in multiple tumor types to detect MRD, including nasopharyngeal carcinoma (27), colorectal carcinoma (28)(29)(30)(31)(32), locally advanced rectal carcinoma (33), breast carcinoma (34), pancreatic carcinoma (35,36), and lung carcinoma (37) ( Table 1). ctDNA in the plasma has a short half-life (<2 hours); however, it has been found that ctDNA may be elevated 24 hours following intervention in early post-operative samples, most likely due to release of ctDNA from damaged tissue (28).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular Residual Disease (MRD). ctDNA has been shown in multiple tumor types to detect MRD, including nasopharyngeal carcinoma (27), colorectal carcinoma (28)(29)(30)(31)(32), locally advanced rectal carcinoma (33), breast carcinoma (34), pancreatic carcinoma (35,36), and lung carcinoma (37) ( Table 1). ctDNA in the plasma has a short half-life (<2 hours); however, it has been found that ctDNA may be elevated 24 hours following intervention in early post-operative samples, most likely due to release of ctDNA from damaged tissue (28).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of patients with colorectal cancer (CRC) in whom ctDNA can be detected depends on the extent of tumour volume and ranges from 50% in those with non-metastatic disease to nearly 90% in patients with metastatic disease 9 . In those who have undergone curative resection, earlier studies suggest that the postoperative detection of ctDNA ranges from 10-15% of patients with stage II disease to nearly 50% in those with stage IV disease [9][10][11][12][13][14][15][16] . Building on these studies, data on the potential uses of ctDNA are rapidly accumulating in the continuum of care across multiple cancers, including CRC (Fig.…”
mentioning
confidence: 99%
“…While other tumour-informed assays using Safe-SeqS, ddPCR and other designs exist, the Signatera test has been widely studied in many GI and non-GI tumour types, demonstrating impressive sensitivities (88-100%) and specificities (93-100%) for MRD, positive predictive values for relapse (>98%) and median lead times from ctDNA detection to relapse (8-9 months). [20][21][22]24,29,34,36,50,[52][53][54][55][56][57][58][59][60][61][62][63][64][65] These highly specific and sensitive assays are particularly attractive for MRD detection and are being increasingly studied in this space. However, due to the inherent process of tumour, germline and then peripheral blood sequencing, tumour-informed testing may be more expensive than the plasma-only approach, as it first requires tumour tissue acquisition and testing, and takes longer to obtain results (4-6 weeks for the first and then 7-10 days for subsequent test results).…”
Section: Minimal Residual Disease Detection Methodsmentioning
confidence: 99%